Automatic beat-to-beat left heart av normalization: is it possible? - Chirife R; Tentori MC; Mazzetti H; Dasso D (Pacing & Clinical Electrophysiology, 2003)
CHIRIFE, R., et al.: Automatic Beat-to-Beat Left Heart AV Normalization: Is It Possible? Programming the right heart AV interval to a normal value may cause a nonphysiological left heart AV due to interatrial and interventricular conduction delays, thus affecting cardiac performance. Since AV normalization at rest and exercise may be invalidated by pacing or sensing (mode) changes, the aim of this study was to (1) study the feasibility of a mode independent pacemaker (PM) algorithm for automatic beat-to-beat left AV normalization, (2) establish normal values for the time between mitral flow A wave (Af) and ventricular activation (Va), the AfVa interval, the mechanical surrogate of left AV, and (C) determine the range of values of the interatrial electromechanical delays (IAEMDs) and the effect of RA pacing. To pace with the proper right AV, the previously reported RV-paced interventricular electromechanical delay and the interatrial electromechanical delay, either P-sensed (IAEMDs) or atrial-paced (IAEMDp) are required inputs. Data were collected during diagnostic echo Doppler studies in 84 subjects divided in three groups: (1) control with narrow QRS and no structural heart disease (n = 33, age 50 ± 21 years, 42% men); (2) patients in sinus rhythm with diverse cardiac pathologies except LBBB (n = 39, age 69 ± 14 years, 56% men), and (3) DDD-paced patients (n = 12, mean age 71 ± 6 years). Normal values of AfVa were established from the control group, while IAEMDs and IAEMDp and active atrial flow time (A-peak), in all subjects. The algorithm was tested by computer simulation under all possible modes with the following calculation: RAV = N + IAEMD - IVD, where RAV is the right AV, N is the desired normal AfVa value, IAEMD is either P-sensed or A-paced, and IVD is close to zero for intrinsic narrow QRS and biventricular pacing, or 79 ms for RV pacing. The results demonstrated (1) Normal (controls) AfVa: 85 ± 15 ms (range 52-110 ms); (2) IAEMDs (All): 84 ± 16 ms; (3) atrial pacing prolonged IAEMDs by 57 ± 18 ms (from 93 ± 15 to 150 ± 25 ms, P < 0.0001); and (4) Computer simulation of rate and mode changes validated the normalization algorithm. An automatic, beat-to-beat left AV normalization algorithm to preserve a normal AfVa without a hemodynamic sensor is feasible. The normal value of AfVa is 85 ± 15 ms. (PACE 2003; 26:2103-2110)